ANALISIS STRATEGI MANAJERIAL KEPALA SEKOLAH DALAM MENGINTERNALISASI KARAKTER RELIGIUS DAN DISIPLIN DI SMP - Restaviana, Imanda; Rahayu, Sri; Chintya, Ria; Lestari, Neta Dian; Zulinto, Ahmad (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
The implementation of religious and disciplinary character education is a fundamental pillar in the national education reform agenda, yet the challenges posed by the social environment and technology in central Palembang are potentially eroding these noble values. This research aims to deeply analyze the managerial strategy applied by the Principal of SMP Negeri 21 Palembang in internalizing religious and disciplinary character values using the POAC approach (Planning, Organizing, Actuating, and Controlling). This study uses a qualitative approach with a descriptive case study design, focusing on SMP Negeri 21 Palembang. Primary data was collected through in-depth interviews, participant observation, and questionnaires distributed to key informants, including the Principal, Vice Principal, Islamic Religious Education Teacher, Counseling Teacher, and student representatives. Data analysis was performed using the interactive model of Miles, Huberman, and Saldana, and the validity was ensured through source, technique, and theory triangulation. The results show that the Principal's managerial strategy has been implemented comprehensively. In the Planning stage, character values are explicitly integrated into the school's vision, mission, and supported by specific budget allocations in the RKS/RKAS. Organizing is realized through the formation of a Character Task Force Team with clear functional and coordinative duties. The Actuating phase is strengthened by strong leadership through example (modeling) and routine habituation activities (congregational Dhuha prayers, 5S). However, a competence gap was found, with about 20% of teachers struggling to integrate character values into their lesson plans (RPP). Controlling is formally effective through the Daily Control Book and PKKS, although there is inconsistency in sanction enforcement among the implementing teachers, which may reduce the credibility of the disciplinary system. Overall, the strategy is highly effective in building a character-based school ecosystem, but its success will be optimized with continuous teacher competency improvement and strengthened consistency in applying reward and punishment at all levels. ABSTRAK Pendidikan karakter religius dan disiplin telah menjadi isu sentral dalam agenda reformasi pendidikan nasional, didorong oleh kesadaran bahwa tujuan pendidikan adalah membentuk watak dan peradaban bangsa yang bermartabat, namun krisis moralitas dan peningkatan perilaku indisipliner memerlukan strategi manajerial yang matang. Penelitian ini berfokus pada Analisis Strategi Manajerial Kepala Sekolah dalam Menginternalisasi Nilai Karakter Religius dan Disiplin di SMP Negeri 21 Palembang melalui fungsi manajemen POAC (Planning, Organizing, Actuating, dan Controlling). Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus deskriptif yang dilaksanakan di SMP Negeri 21 Palembang. Sumber data primer diperoleh dari wawancara mendalam, observasi partisipatif, dan angket kepada Kepala Sekolah, Wakil Kepala Sekolah, Guru, dan Siswa. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldana, serta diverifikasi melalui teknik triangulasi. Hasil penelitian menunjukkan bahwa strategi manajerial telah terlaksana secara komprehensif: Perencanaan diwujudkan dengan integrasi nilai dalam visi/misi dan alokasi anggaran spesifik (RKS/RKAS). Pengorganisasian efektif melalui pembentukan Tim Satgas Disiplin dan pendelegasian tugas fungsional yang jelas. Pelaksanaan diperkuat oleh keteladanan Kepala Sekolah (modeling) dan pembiasaan rutin (Salat Dhuha, 5S). Namun, teridentifikasi kesenjangan pada tahap Actuating (20% guru kesulitan integrasi kurikulum) dan Controlling (inkonsistensi penegakan sanksi oleh guru pelaksana). Simpulan utamanya adalah strategi manajerial Kepala Sekolah menunjukkan efektivitas tinggi dalam membangun ekosistem sekolah yang berkarakter, namun perlu ditingkatkan melalui penguatan kompetensi guru dan konsistensi penerapan reward dan punishment di semua tingkatan agar hasilnya lebih optimal dan berkelanjutan.